The effectiveness of food industry wastewater treatment by means of different kinds of cavitation generators - Starchevskyy, Volodymyr; Bernatska, Nataliya; Typilo, Iryna; Khomyshyn, Iryna (Lviv Politechnic Publishing House, 2017)
Досліджено ефективність очищення стіч- них вод за допомогою ультразвуку та віброкавітації. Засто- сування віброкавітації дає такий же ефект, як і використання ультразвукової кавітації, але економічно доцільніше використовувати вібраційний низькочастотний кавітатор.

The effectiveness of wastewaters treatment by means of ultrasonic and vibration response cavitation has been investigated. The application of the vibration and cavitation equipment produces the same effects as in case of ultrasonic cavitation, but it is economically reasonable to use vibration response low-frequency cavitators.
Ефективність оброблення стічної води підприємств харчової промисловості різними типами генераторів кавітації
Keywords: акустична кавітація; очищення води; кінетика реакції; біологічне забруднення; хімічне споживання кисню; кавітатори; acoustic cavitation; water purification; reaction kinetics; biological contamination; chemical oxygen demand; cavitators